2016
DOI: 10.15761/nfo.1000128
|View full text |Cite
|
Sign up to set email alerts
|

A paradigm shift in the management of neovascular glaucoma

Abstract: Neovascular glaucoma (NVG) secondary to proliferative diabetic retinopathy (PDR) is a potentially devastating condition. The commonest cause of treatment failure in NVG is underlying systemic disease progression. The underlying ischemia is often refractory to medical treatment. Surgical options have evolved to include Bevacizumab in the Ophthalmologist's armamentarium. Visual prognosis can be guarded in these patients who additionally have reduced life expectancy. Thus, early diagnosis and aggressive treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Besides, NVG is more likely to occur after cataract surgery and vitreoretinal surgery due to surgery-induced inflammation cascade, retinal hypoxia, and the lack of anti-neovascular factors ( 14 , 15 ). Furthermore, clinical studies have shown that posterior surgery might help the diffusion of vascular endothelial growth factor (VEGF) into the anterior chamber ( 18 ). Taking the above risk factors, the incidence of NVG in diabetic patients after ocular surgery raised to 80% ( 19 ).…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
“…Besides, NVG is more likely to occur after cataract surgery and vitreoretinal surgery due to surgery-induced inflammation cascade, retinal hypoxia, and the lack of anti-neovascular factors ( 14 , 15 ). Furthermore, clinical studies have shown that posterior surgery might help the diffusion of vascular endothelial growth factor (VEGF) into the anterior chamber ( 18 ). Taking the above risk factors, the incidence of NVG in diabetic patients after ocular surgery raised to 80% ( 19 ).…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
“…Diabetic retinopathy is often associated with neovascular proliferation due to ischemia in the retina and release of angiogenic factors. These conditions cause neovascularization of the optic disc (NVD), also neovascularization elsewhere (NVE) [70,71]. Patients with NVD have a poor visual prognosis due to high incidence of complication, such as vitreous hemorrhage, fibrous proliferation, and traction retinal detachment.…”
Section: Definitionmentioning
confidence: 99%
“…In DR, capillary occlusion and reduced perfusion in retina provoke cascade events related to hypoxia and lead to angiogenesis. Normally, pro-angiogenic factors (VEGF and angiopoietin-2) and antiangiogenic factors (pigment epithelium-derived growth factor) are in equilibrium [71]. Imbalance between those factors might trigger activation, proliferation, and migration of endothelial cells and pericytes and lead to neovascularization [71][72][73].…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations